PROPOSED A COMPACT MULTIBAND AND BROADBAND RECTANGULAR MICROSTRIP PATCH ANTENNA FOR C-BAND AND X-BAND. - Tiwari, Rahul; Verma, Seema (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this communication two proposed antenna described one for broadband at 6.71445GHz to 11.9362GHz with finite ground plane. TheÂ antennaÂ designed with 11.4051mmÃ— 8.388 mm radiating copperÂ patchÂ with ground plane design with 21.0051mm x17. 988mm. And this Compact broadbandÂ rectangularÂ shapeÂ microstripÂ patchÂ antennaÂ is designed and analyzed for the return lossÂ ofÂ -20.08 dB is achieved at the resonant frequencyÂ ofÂ 7.941GHz, From Antenna2-it is observed that, antenna for multiband at different frequency. The primary radiating elements are Simple Rectangular Microstrip Patch Antenna in upper side with probe feed and use finite ground plane are two parallel crossed printed slot for three different frequency applications which is smaller in size compared to other availableÂ multibandÂ antennas. From the result, it is observed that, the return lossÂ ofÂ -16.97 dB is achieved at the first resonant frequencyÂ ofÂ 4.853GHz, -10.30dB at the second resonant frequencyÂ ofÂ 8.382GHz, -10.73 dB at the third resonant frequencyÂ ofÂ 9.265GHz, -17.38 dB at the fourth resonant frequencyÂ ofÂ 10.15GHz and -12.37 dB at the fifth resonant frequencyÂ ofÂ 11.91GHz. This broadband and multi-band highly efficient antennaÂ forÂ use in C-Band, and X-Band.